Information and Communication Technology (ICT) Competencies of Students: A Case Study at Bachelor of Science in Office Administration Students in Pre-Internship - Bornales, Sarah Mae R.; Manuel, Roselyn P.; Torres, Dimple S.; Marpuri, Jessica C. (The Indonesian Institute of Science and Technology Research, 2025)
The study aims to assess the Information and Communication Technology (ICT) competencies of Bachelor of Science in Office Administration (BSOA) third-year students at Camarines Sur Polytechnic Colleges (CSPC) in preparation for their pre-internship. The research problem centers on evaluating students’ readiness in identifying factors that influence their ICT proficiency, which is crucial for success in the modern professional workplace. The hypothesis assumes no significant relationship exists between the competency levels and the factors affecting the competencies. Using quantitative, correlational research design, data was collected through a structured online questionnaire distributed to 144 BSOA students. The study analyzed various competency levels: basic, intermediate, and advanced ICT skills. The results revealed that the majority of the students show basic to intermediate ICT proficiency, with several factors such as personal background, socio-economic status, and access to technology playing a role in their competency levels. A significant relationship was found between these factors and ICT competency, rejecting the null hypothesis. The study concludes that targeted interventions are necessary to enhance students’ ICT skills before their internships. The findings have implications for curriculum design, suggesting that integrating more advanced ICT training could better prepare students for the digital workplace demands.